Exciton hybridization in a WS2/MoS2 heterobilayer mediated by a surface wave via strong photon–exciton coupling - Yi Junxuan; Liu Shimei; Li Shulei; He Weichen; Chen Zuxin; Lan Sheng (Nanophotonics)
The hybridization of multiple excitons in a heterobilayer composed of two transition metal dichalcogenides (TMDCs) based on strong light–matter interaction is interesting from the viewpoint of both fundamental research and practical application. Here, we investigate numerically and experimentally the hybridization of three excitons in a heterobilayer mediated by the surface plasmon polaritons (SPPs) excited on a thin Au film and the transverse-electric (TE) polarized waves excited on a Si3N4/Ag heterostructure via photon–exciton coupling. Relying on numerical simulation, we observe anticrossing behaviors in the angle-resolved reflection spectra calculated for MoS2/WS2/Au and WS2/MoS2/Si3N4/Ag heterostructures, which reveal the coupling between the surface wave (SPPs or TE waves) and the multiple excitons in the heterobilayer. In experiments, we employ the oligomers of polystyrene (PS) nanospheres as scatters to transfer the surface waves into far-field radiations. Similarly, we observe anticrossing behaviors in the angle-resolved scattering spectra measured for the oligomers of PS nanospheres. Relying on the coupled oscillator model, we observe Rabi splitting energies of ΩSPP ∼206.79 meV for the SPPs and ΩTE ∼237.60 meV for the TE waves. Based on the calculated current density distributions and Hopfield coefficients, we demonstrate the hybridization of the three excitons in the WS2/MoS2 heterobilayer mediated by the TE waves. Our findings open new horizons for manipulating light–matter interaction in TMDC heterobilayers and suggest the potential applications of exciton hybridization in energy transfer.